A Comparison of Treatment Options for Type 1 and Type 2 Caesarean Scar Pregnancy: A Retrospective Case Series Study - Shen, Fanghua; Lv, Hongdao; Wang, Liming; Zhao, Ruiheng; Tong, Mancy; Lee, Arier Chi-Lun; Guo, Fang; Chen, Qi (Frontiers in Medicine, 2021)
Background: There is currently no agreement on the optimal management of caesarean scar pregnancy. Caesarean scar pregnancy is currently categorised into two subtypes according to the site of implantation. This may consequently result in the difference in treatment options. However, the comparison of the success rate of each treatment option according to the subtypes has not been fully investigated. Methods: 71 patients who were treated by uterine curettage (D and C), or uterine artery embolization with curettage (UAE) or hysteroscopy in conjunction with laparoscopy between January 2016 and March 2020 were included. Data on maternal age, gestational sac age, the sac diameter, the interval between two pregnancies, the number of previous caesarean sections, amount of bleeding and β-hCG levels were collected and analysed dependent on the subtypes. Results: There was no difference in the clinical parameters of the cases who received different options of treatment, as well as no difference in the clinical parameters between type 1 and type 2 caesarean scar pregnancy. The primary success rate for type 1 caesarean scar pregnancy by D and C, or UAE, or hysteroscopy in conjunction with laparoscopy was 95, or 100 or 100%, respectively. The primary success rate for type 2 caesarean scar pregnancy by D and C, or UAE, or hysteroscopy in conjunction with laparoscopy was 27, or 67, or 95% respectively. Conclusion: Our data demonstrates that hysteroscopy in conjunction with laparoscopy for type 2 caesarean scar pregnancy was the most successful compared to other options, but for type 1 caesarean scar pregnancy, D and C could be the cost-effective option.